Honey Supplementation to Semen-Freezing Medium ImprovesHuman Sperm Parameters Post-Thawing. - Muhammad-B; Rana A-R Alsaadi (Tehran University of Medical Sciences, 2014)
Objective: To evaluate the effect of honey supplemented to cryoprotectant medium on post-thaw sperm motility, concentration, morphology and agglutination. Materials and methods:Thirty semen samples were collected from 30 infertile patients. After assessment of semen analysis, semen samples were divided into 3 aliquots (0.7ml for each) and mixed with 1 ml of cryopreservation solution (G1, control) alone, or enriched with 5% honey (G2) or with 10% honey (G3) for cryopreservation. Cryopreservation was done at -196°C in liquid nitrogen and thawing was performed after six months. Direct swim up technique was used for in vitro sperm preparation post-thawing. Sperm parameters were assessed and data were statistically analyzed pre- and post-thawing. Results: Results appeared that the percentage of sperm motility for G1 and G2 groups were significantly reduced (P < 0.05) post-thawing when compared to pre-cryopreservation. However, there was no significant difference in the total motility (%) of the post-thaw sperm between the G1 and G2 groups. While there was significant increased (P < 0.05) in the percentage of normal sperm morphology for G1 and G3 groups post-thawing. Post-thawing normal sperm morphology (%) for G3 group was significantly increased (P < 0.05) as compared to G1 and G2 groups. In contrast non significant differences (P > 0.05) were observed between G1 and G2 groups. Significant reduction (P < 0.05) was seen in the sperm concentration for all groups post-thawing as compared to pre-cryopreservation groups. After thawing the results reveal significant reduction (P < 0.05) in the sperm agglutination (%) for G3 group as compared to G1 and G2 groups. Conclusion: The results of this study indicated that the supplementation of honey (10%) to cryoprotectant solution results in enhancement of sperm quality post-thawing.